Ethnic differences in the epidemiology of cutaneous lupus erythematosus in New Zealand. (November 2016) - Jarrett, P; Thornley, S; Scragg, R
Background: The prevalence and variation by ethnicity of cutaneous lupus in New Zealand is not known. Therefore, a cross-sectional study to determine the prevalence and variation by ethnicity of cutaneous lupus in the ethnically diverse community of South Auckland, New Zealand, was undertaken. Methods: Multiple sources were examined to determine the prevalence of acute cutaneous lupus erythematosus, subacute cutaneous erythematosus and discoid lupus erythematosus. Ethnicities examined were European, Māori/Pacific and Indian/Asian. Capture–recapture was used to determine the overall population prevalence of cutaneous lupus. Results: A total of 145 cases of cutaneous lupus were identified. There were 22 men and 123 women, with an average age (standard deviation), respectively, of 46.4 (±21.5) and 43.1 (±14.8) years. There were 53 cases of acute cutaneous lupus erythematosus, 19 cases of subacute cutaneous erythematosus and 66 cases of discoid lupus erythematosus. The age and sex adjusted relative risk (95% confidence interval; CI) of Māori/Pacific compared to the European population was 2.47 (95% CI 1.67–3.67) for all types of cutaneous lupus, 1.60 (95% CI 0.84–3.18) for acute cutaneous lupus erythematosus, 0.09 (95% CI 0.01–1.1) for subacute cutaneous erythematosus and 5.96 (95% CI 3.06–11.6) for discoid lupus erythematosus. The overall prevalence of cutaneous lupus was 30.1 (95% CI 25.5–35.4) per 100, 000. However, capture–recapture estimated the unadjusted prevalence of cutaneous lupus to be 86.0 (95% CI 78.1–94.7) per 100, 000. Conclusion: Māori and Pacific people in Auckland, New Zealand, have a greater relative risk of all types of cutaneous lupus compared to the European population and a particularly high risk of discoid lupus erythematosus.